ANALISIS KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG DI JAKARTA TIMUR - Renaldo, (2021)
A quantitative study designed to prove whether product quality, brand image and price influence Samsung smartphone purchasing decisions. The population in this research are consumers who use smartphones with the Samsung brand in East Jakarta. A total of 75 respondents were selected as samples in this research. In determining the sample used non-probability technique with purposive sampling method. Data collection in this study was carried out by distributing a questionnaire that had been made using the gform. The analysis technique used in this research is descriptive and inferential assisted by the Smart PLS 3.0 application. This research proves that product quality, brand image and price have a significant effect on purchasing decisions and have a coefficient value of 0.305 for product quality, 0.298 for brand image and 0.288 for price.